# Yahoo Web Search

1. ### How do I show that [( k )(u)]* v = k (u* v )?

I' m assuming * is the...vector w, and assume that u and v have the same length n. You...the sum, from j = 1 to n, of ( k u_j) v _j [from the definition of...multiplication of real numbers: a single number k can be...

1 Answers · Science & Mathematics · 02/05/2011

A - K - V -E-S-H-C- M -R-B-P-F. At Kilamajaro, Victor...

1 Answers · Education & Reference · 20/01/2012

3. ### An object of mass m , oscillating on the end of a spring with spring constant k has amplitude A . Its maximum sp?

... the list of possible equations... x = Acos(√( k / m )t) v = - A √( k / m )sin(√( k / m )t) a = -Ak/ m * cos(√( k / m )t) The max speed is...

1 Answers · Science & Mathematics · 10/12/2012

4. ### what is solution to mv' = -9.8m + kv with respect to t ? v (0)= v (0)?

... So, B = 9.8/ k Now add both solutions: v = A e^kt/ m + 9.8/ k And use the initial conditions: v (0) = v (0) to evaluate A ...

4 Answers · Science & Mathematics · 31/12/2006

5. ### 2 Select which group does not belong:?

A K L M H :)))

3 Answers · Science & Mathematics · 24/09/2007

6. ### I need more help with this 1/(g-( k / m ) v ^2) dv?

Essentially you want to write the integral as: ( m / k )*dv / [ mg/ k - v ^2] And replace mg/ k with a ^2. The easiest method is to get the hyperbolic trig function directly...

1 Answers · Science & Mathematics · 21/06/2007

7. ### Solving equations by adding or subtracting? k - 16= 7?

k - 16= 7 k = 23 y + 12 = -10 y= 22 x + 8 = -1 x= -9 v + 13 = -11 v = -24 p + 14 = -1 p= -15 h - 9 = 12 h= 21 c + 5 = 2 c= -3 a - 12 = -19 a = -7 q + 3 + -5 q = -8 m - 10 = 4 m = 14 j+11= 4 j= -7

5 Answers · Science & Mathematics · 27/09/2011

8. ### Find the next Item in this sequence: A , K ,Q,J, ____ deer, drop, name, long,needle ,note____ M , V ,E, M ,J,S,U,______

A , K ,Q,J, ____ 10 Cards deer, drop, name, long,needle ,note____ drink Do, Re, Mi words M , V ,E, M ,J,S,U,______ N ...

4 Answers · Education & Reference · 25/04/2007

9. ### pleasseeee helppp with this problem: an object with mass m subjected to a force F=kte^-at, find v (t) a (t)?

F = ma(t) = kte^(-at) => a (t) = k / m * te^(-at) v (t) = ∫ a (t) dt = k /(ma^2) * (-ate^(-at) - e^(-at) + C) = - k /(ma^2) * e^(-at)*(at + 1 + Ce^(at))

1 Answers · Science & Mathematics · 07/10/2013

10. ### The amplitude and period of a puck traveling 5.4m/s that slides into a spring with a constant of 15N/ m ?

...motion is described by : deflection = s = A .sin(ωt) where ω = √( k / m ), A = amplitude and t = time. The velocity is: v = ds/dt = A .ω.cos(ωt) so A .ω = A .√( k / m ) = 5.4 at...

1 Answers · Science & Mathematics · 30/04/2011